2020
DOI: 10.1097/phh.0000000000001261
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Syringe Service Programs and Supervised Use Sites Among a Sample of Registered Voters in a US State

Abstract: Context:The decision to initiate a syringe service program or expand to a supervised use site is often influenced by local public support or opposition. Objective: The purpose of this study was to better understand public attitudes to local syringe service programs to inform the possibility of expanding services. Design, Setting, and Participants: We surveyed a sample of registered voters (n = 690) in the 8 counties in the state of Colorado with existing syringe service programs. Main Outcome Measures:Responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Overall, about 64% of respondents with an opinion expressed some level of support for these facilities within the United States (i.e., a response of between +1 and +10), while 53% expressed some level of support for a local neighborhood facility. This result is similar to a 2019 survey in eight counties in Colorado, which found that 57% of respondents thought "supervised use sites" should be legal in their state (Brooks-Russell et al, 2021). Yet our findings also suggest that support for local facilities may be increasing as well.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overall, about 64% of respondents with an opinion expressed some level of support for these facilities within the United States (i.e., a response of between +1 and +10), while 53% expressed some level of support for a local neighborhood facility. This result is similar to a 2019 survey in eight counties in Colorado, which found that 57% of respondents thought "supervised use sites" should be legal in their state (Brooks-Russell et al, 2021). Yet our findings also suggest that support for local facilities may be increasing as well.…”
Section: Discussionsupporting
confidence: 85%
“…on Canadian residents (e.g., Cruz et al, 2007;Kerr et al, 2017;Manson-Singer & Allin, 2020;Mrazovac et al, 2020;Strike et al, 2015), or has examined the views and experiences of potential users of these facilities, rather than general community members (e.g., Frost, 2017;Klein et al, 2020;Van Den Boom et al, 2021). The research specifically focusing on perceptions in the United States has been largely limited by nonrepresentative and/or convenience samples (Kulesza et al, 2015), and generalizability concerns due to focusing on residents in a given city or state (Brooks-Russell et al, 2021;Frost, 2017;Roth et al, 2019), or select counties (Taylor et al, 2021). Additionally, an individual's support for these facilities in general likely differs from their support for operating such a facility within one's local neighborhood (see Dear, 1992;Tzemis et al, 2013), the latter of which may be influenced by "Not In My Backyard" (NIMBY) concerns.…”
mentioning
confidence: 99%
“…Finally, opioid overdose deaths surged during the pandemic. Researchers hypothesize that this is due to a decline in mental health due to isolation, economic distress from the pandemic, changes to the drug supply chain causing unsafe mixtures of drugs, and lack of access to substance use treatment programs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on SSPs, however, has indicated that because SSPs vary widely (i.e., state vs. local, urban vs. rural, mobile vs. fixed locations), there may be wide discrepancies in how they are operated and the challenges they face, such as community attitudes towards the programs [16,20]. This could mean that, despite CDC guidance, individual SSPs may have approached operations differently during the pandemic due to varying population characteristics between locations [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%